INTEGRATING RELIGIOUS CULTURE IN EVERY SCHOOL ACTIVITY: STEPS TOWARDS CHARACTER EDUCATION - Zakiyah, Lailis; Khoiroh, Ummul; Rofiki, Moh.; Diana, Eka (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the application of religious values in every aspect of life at MI Miftahul Ulum Opo-opo and its impact on the formation of student character. The research method used is qualitative with data collection through interviews and observation. This research focuses on routine religious activities carried out in schools, such as congregational prayers, reciting the Koran, and the integration of religious teaching in general subjects. The research results show that the application of religious values in the school environment has a positive impact on the formation of students' character, especially in terms of discipline, responsibility, empathy and concern for others. Students become more disciplined in carrying out daily activities, respect time, and show concern for the environment and other people. Apart from that, close collaboration between the school and parents also strengthens the formation of students' religious character. Parents support religious activities at school and accompany children in religious activities at home. Overall, MI Miftahul Ulum Opo-opo has succeeded in creating an environment that not only supports students' intellectual development, but also strengthens character formation based on Islamic religious teachings. In this way, students are ready to face life's challenges with commendable morals and a strong religious foundation, making them individuals who are not only academically intelligent, but also have good morals.